Assessment of factors related to poly cystic ovarian syndrome - A comparative and correlational study - Aparna Eledath Kolasseri; Anjana Eledath Kolasseri; Jayanthi Sivaraman; Tamizhselvi Ramasamy (Taylor & Francis Group, 2024)
AbstractPolycystic ovarian syndrome (PCOS) is a common endocrine disorder that primarily affects women of reproductive age. It is particularly prevalent among adolescent females who receive an insufficient diagnosis despite having potentially adverse consequences. The use of PCOS screening questionnaires has the potential to aid in the early detection of symptoms. The goal of this study is to observe if a self-administered questionnaire may be useful for a clear cognizance of the associated conditions like mental stress and menstrual characteristics correlated to polycystic ovary syndrome. In this study, we selected women within an age group of 17-40 with and without PCOS based on the modified Rotterdam criteria to fill out a self-administrated questionnaire based on the signs and symptoms of PCOS majorly focusing on mental stress and menstrual characteristics. SPSS software, univariate analyses were employed to elucidate the associations among the components of PCOS, demographic factors, and lifestyle characteristics, hence providing insights into the interrelationships among those variables. 64 women with PCOS and 141 women without PCOS participated in the present study. The present study revealed PCOS is greatly influenced by age at menarche (p-value= .043), typical cycle length (p-value = .000) mental health problems during menstruation (p-value = .032), and body mass index (p-value = .001). Multivariate hierarchical logistic regression analysis showed only 2 variables BMI (a-OR 1.156,95% CI (1.067-1.242), p-value = .000), and typical cycle length (a-OR 2.278, 95% CI (1.079-4.809), p-value = .003) were significant. The present study showed that BMI and menstrual cycle length were most closely associated with the incidence of PCOS, which is important in diagnosing and treating the condition. Considering the high incidence of PCOS among women of reproductive age and its potential for significant health implications, it would be prudent to incorporate inquiries regarding mental health concerns and menstrual patterns into routine medical assessments for this demographic analysis. This approach aims to ascertain whether additional diagnostic evaluations and screenings for PCOS are warranted.